Low Molecular Weight Heparin and Warfarin in the Treatment of Patients with Antiphospholipid Syndrome during Pregnancy - Pauzner, Rachel; Dulitzki, Mordechai; Langevitz, Pnina; Livneh, Avi; Kenett, Ron; Many, Amira (Thrombosis and Haemostasis, 2001)
Fifty-seven pregnancies in women with antiphospholipid syndrome (APS) are presented. These were treated with s.c. enoxaparin and low dose aspirin. In fourteen pregnancies warfarin was prescribed between weeks 15-34 (warfarin group). The decision to switch to warfarin depended on a morbidity score, and the patient’s consent. Neither teratogenicity nor significant maternal, fetal or neonatal hemorrhage was observed. Despite the higher pretreatment morbidity score of the warfarin group, the live birth rate was high in both groups: 86% in the warfarin group and 87% in the non-warfarin group. There was no significant difference in week of delivery, birth weight, or incidence of thrombosis between the groups. The study demonstrates the efficacy and safety of anticoagulants during pregnancy. The use of LMWH in pregnant women with APS not being moot, warfarin might be justified in selected patients.
Keywords: Antiphospholipid syndrome; pregnancy; low molecular weight heparin; warfarin